Education and grip strength among older Thai adults: A mediation analysis on health-related behaviours - Wiraporn Pothisiri; Orawan Prasitsiriphon; Nandita Saikia; Wichai Aekplakorn (Elsevier, 2021)
Abstract Background: Previous studies have investigated the effect of differential educational attainment at younger ages on health disparities among older adults, but how such an effect can be attenuated remains understudied. This study examines the mediating effects of four health-related behaviours, namely smoking, alcohol drinking, healthy eating, and physical activity, on the relationship between older adults' education and grip strength. Methods: The study used data from 7,064 individuals aged 60 years and older who participated in the 2009 National Health Examination Survey of Thailand. To examine the relationships among education, health behaviours, and grip strength, multivariate regressions were performed following Baron and Kenny's approach. Generalized Structural Equation Modelling (SEM) was utilized to quantify the mediating effects. Results: All else being equal, education is positively associated with stronger grip for both genders. The mediation analyses demonstrate that health-related behaviour plays an important role in the relationship between education and grip strength; however, the extent to which it mediates the effect of education varies with the type of health behaviour and between genders. Not smoking and engaging in physical activity can partly explain the relationship between education and grip strength in older men. Meanwhile, the consumption of fruits and vegetables and participation in regular physical activity significantly mediate the effect of education on grip strength in older women. Conclusion: Our study reaffirms the importance of educational opportunity in earlier life and recommends health-related behavioural modifications to improve health status in low-educated older adults.